The Influence of Digital Financial Literacy and Government Support on the Financial Performance of Retail MSMES in Padang City With Digital Payment Adoption as a Mediating Variable - Fadhillatul Hidayati; Tafdil Husni; Fajri Adrianto (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2026)
This study aims to examine the effect of digital financial literacy and government support on the financial performance of micro, small, and medium enterprises (MSMEs) in the retail sector in Padang City, with digital payment adoption as a mediating variable. Digital payments in this study include the use of e-wallets and QRIS. This research employs a quantitative approach using non-probability sampling with a purposive sampling technique. A total of 100 respondents were obtained through the distribution of questionnaires via Google Forms to retail-sector MSME owners in Padang City who have adopted digital payment systems. Data analysis was conducted using the Structural Equation Modeling– Partial Least Squares (SEM-PLS) method with SmartPLS version 4.0 software. The results indicate that digital financial literacy and government support have a positive and significant effect on digital payment adoption. Furthermore, digital financial literacy, government support, and digital payment adoption have a positive and significant effect on financial performance. Mediation analysis reveals that digital payment adoption significantly mediates the relationship between digital financial literacy and financial performance. However, digital payment adoption does not significantly mediate the relationship between government support and financial performance, indicating that the influence of government support on financial performance is more dominantly exerted through a direct pathway rather than through the mechanism of digital payment adoption.